Adolescent Emotional Control Moderates Benefits of a Multicomponent Intervention to Improve Type 1 Diabetes Adherence: A Pilot Randomized Controlled Trial. (21st September 2018) - Lansing, Amy Hughes; Stoianova, Maria; Stanger, Catherine
Abstract: Objective: We previously tested via randomized controlled trial a novel intervention for adolescents with type 1 diabetes and above-target glycemic control that combined web-delivered incentives for self-monitoring of blood glucose (SMBG) and brief web counseling with working memory training and parental contingency contracting training. Results showed improved SMBG and decreased glycosylated hemoglobin (HbA1c) at 6- and 12-month follow-ups. However, it has not been elucidated if improvements in SMBG mediated the immediate benefits of this treatment on HbA1c nor if this intensive intervention uniquely benefited a subgroup of adolescents with higher problems in emotional control. Methods: Adolescents with type 1 diabetes and above-target glycemic control ( n = 61) were randomized to receive the 6-month intervention ( n = 30) or usual care ( n = 31). Adolescents completed the Behavior Rating Inventory of Executive Function-Self-Report, problems with emotional control subscale at baseline, and provided meter downloads to assess frequency of SMBG and completed an HbA1c blood draw at baseline and 6 months later. Results: At 6-month follow-up, improvements in SMBG mediated the effects of receiving the treatment on having lower average HbA1c. Further, problems in emotional control moderated the benefits of the intervention on improvements in SMBG and in turn HbA1c. Only adolescents with above average problems in emotional control evidenced improvements in SMBG in response to treatment, which then explained lower HbA1c levels at 6-month follow-up. Conclusions: This multicomponent, web-delivered intervention provided unique benefits for improving SMBG and lowering HbA1c in teens with higher problems in emotional control.